Kompleksitas Pengembangan Peraturan Daerah yang Responsif di Kabupaten Malaka, Nusa Tenggara Timur - Bernardus Seran Kehik; Adeodata Laniria Charla Barros Mbiri (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This research examines the complexity of challenges in developing responsive regional regulations in Malaka Regency, East Nusa Tenggara, Indonesia. The study was motivated by the rejection of Malaka Regency’s draft regional regulations by the Ministry of Law and Human Rights. Using the theoretical framework of regional autonomy, the mechanisms of regulation formation, and Arnstein’s “Ladder of Community Participation” theory, the research explores the sociological, philosophical, and juridical foundations underlying the regulation development process. This descriptive qualitative study employed methods such as observation, interviews, focus group discussions (FGDs), triangulation, and snowball sampling. Data were analyzed using Creswell’s qualitative techniques. The findings reveal several key issues in the regulation development process, including insufficient adherence to sociological considerations, lack of academic manuscripts to guide regulatory content and significant political party interventions. These factors have resulted in unresponsive regulations that fail to address the community’s needs adequately. Moreover, the low level of community participation—due to limited power redistribution—has further hindered the process. The research highlights the need for more inclusive and collaborative mechanisms to ensure that regional regulations are representative, practical, and aligned with the socio-political context. This study contributes to the field of governance and policy-making by emphasizing the importance of responsive regulation as a tool for addressing local societal challenges. Future research should explore strategies for improving community involvement and addressing political barriers in the formation of regional regulations.